STRIATOCAPSULAR INFARCTION; A SINGLE INSTITUTIONAL EXPERIENCE - Shukir Muhammed Amin, Osama (AVICENA, d.o.o., Sarajevo, 2012)
OBJECTIVE: Striatocapsular infarction is an uncommon form of deep hemispheric strokes. We analyzed the clinical presentation of this stroke to determine its core features and neurological outcome. MATERIAL AND METHODS: This prospective, observational, short-term longitudinal study was carried out from November 1, 2009 to October 30, 2011 in the department of neurology, Sulaimaniya general teaching hospital, Iraq and involved 13 consecutive Kurdish patients who were diagnosed with striatocapsular infarction radiologically; all patients underwent routine blood tests, resting 12-lead ECG, transthoracic echocardiography, and urgent non-contrast CT brain scanning at the time of admission. All patients were reassessed clinically after 3 months. RESULTS: Nine patients (69%) were females and 7 patients (53%) were older than 50 years of age. Infarction of the right lenticular nucleus was more common than the left one. Severe flaccid hemiplegia dominated the clinical presentation. Speech and language dysfunction were found in 4 patients (30%) while inattention and neglect were detected in 8 patients (61%). At 3 months, 4 patients were bed-ridden and 4 were wheel-chair bound; dystonia and involuntary movements did not occur. Only the patient with bilateral infarction demonstrated Parkinsonism. CONCLUSION: Striatocapsular infraction in Iraqi Kurdish patients was more common in females and at the right lenticular nucleus. Hypertension, smoking, and hypercholesterolemia were the commonest risk factors. Dense hemiplegia was the commonest presentation; the functional outcome was poor in the majority. After 3 months of the ischemic event, involuntary movements and dystonia were not seen, and Parkinsonism was found in one patient only.